2018
DOI: 10.5114/ceji.2018.74880
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 levels in the serum and saliva of patients with oral lichen planus compared with healthy controls: a meta-analysis study

Abstract: Interleukin-6 (IL-6) is a cytokine that contributes to the pathogenesis of oral lichen planus (OLP). The aim of this meta-analysis study is the evaluation of IL-6 levels in the serum and saliva of patients with OLP compared with healthy controls. We searched the studies in 5 databases: PubMed/Medline, Scopus, ScienceDirect, Web of Science, and Cochrane Library, from 1983 to Oct 31, 2016. Eleven studies were analysed for the meta-analysis study. The reviewers independently evaluated the quality of each included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 24 publications
2
30
1
Order By: Relevance
“…Lymphocyte‐mediated immune response and locally released cytokines promote keratinocyte apoptosis. Consistently, human biopsies from OLP showed extensive epithelial layer destruction and numerous infiltrated lymphocytes, accompanied by high expression of the inflammatory cytokines TNF‐α and IL‐6, confirming previous reports (Kara, ; Mozaffari et al, ) and pointing to a role of these cytokines in the pathological process of OLP. The results of down‐regulated MASPIN and up‐regulated IKKα in OLP tissues attracted our attention.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Lymphocyte‐mediated immune response and locally released cytokines promote keratinocyte apoptosis. Consistently, human biopsies from OLP showed extensive epithelial layer destruction and numerous infiltrated lymphocytes, accompanied by high expression of the inflammatory cytokines TNF‐α and IL‐6, confirming previous reports (Kara, ; Mozaffari et al, ) and pointing to a role of these cytokines in the pathological process of OLP. The results of down‐regulated MASPIN and up‐regulated IKKα in OLP tissues attracted our attention.…”
Section: Discussionsupporting
confidence: 89%
“…Although the cause and pathogenesis of OLP remain unclear, previous studies have clarified that its aetiology includes stress, hypersensitivity, immune response, viral and bacterial infections (Cheng, Gould, Kurago, Fantasia, & Muller, ; Jaafari‐Ashkavandi, Mardani, Pardis, & Amanpour, ). Moreover, inflammatory cytokines play an important role in the pathogenesis of OLP, such as tumour necrosis factor‐alpha (TNF‐α), interleukin (IL‐6) and IL‐17 (Gueiros et al, ; Kara, ; Mozaffari, Sharifi, & Sadeghi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Two meta-analyses [19,20] showed that serum and salivary cytokines (interleukin-6 and tumor necrosis factor-alpha), as important immunological factors involved in systemic inflammation, were significantly more in the OLP patients as compared to the controls. The present meta-analysis checked the serum and salivary Igs levels in OLP patients compared to controls, and showed no elevation in the serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-6 is involved in B-and T-cell differentiation and is able to inactivate p53 with tumor progression of some cancers [73]. Mozaffari et al revealed in a meta-analysis that IL-6 levels in saliva and serum of OLP patients were significantly higher than in healthy controls, with higher values in saliva than in serum [74]. For this reason, saliva seemed to be more useful than serum for the detection of IL-6.…”
Section: Oral Lichen Planusmentioning
confidence: 99%